(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Noise and vibration with the braking process in passenger vehicles has become an important economic and technical issue in the industry. The objective of current work is to analyze the vibration parameters as natural frequency, mode shapes of brake disc with drilled holes of different diameter & of weared discs at outer end. FEM software package is used for vibration analysis of brake discs the disc brake is modeled using commercial computer aided design (CAD) software, ANSYS.To find natural frequency & mode shapes of brake discs with radial holes with same ratio of inner to outer radius. But these plates are having variable sizes of holes to conclude the effect of that on brake discs. Also to check the effect of uniform wear of disc after long time braking by testing worn out brake i.e. variation in thickness, discs to compare with new brake disc and also variation on holding hole diameter. Experimental set up of disc is done for near inner edge clamped at holding hole and outer edge free boundary condition as fitted in motorcycles & conclude by comparing FEM and FFT results.